Adopting environmental responsibility among Algerian SMEs in light of the challenges of sustainable development - Benmessaoud, Adem; Saidat, Nedjmi; Elfekair, Amina (International journal of economic perspectives, 2024)
In the modern era, numerous global challenges have emerged, impacting nations worldwide. The rapid advancements in technology and industry have led to significant environmental degradation, particularly affecting the oceans—a critical component of sustainable development. In response to these developments, small and medium-sized enterprises (SMEs) have assumed a pivotal role in environmental preservation by mitigating pollution across various sectors. Consequently, our research endeavors to examine the status of Algerian SMEs concerning their environmental commitments and their pursuit of the ISO 14001 certification. This certification has seen substantial growth, buoyed by support from the Algerian government through the establishment of various entities, support structures, and rehabilitation programs in collaboration with international organizations. Despite concerted efforts and the allocation of considerable resources, Algerian SMEs encounter numerous challenges that impede their effectiveness in fostering sustainable economic development.